Structural, functional and stability characterisation of human glutathione S-transferase Pi - Mhlanga, Donald (My University, 2018)
Glutathione S-transferases (GSTs) are Phase II detoxification enzymes that catalyse the conjugation of glutathione (GSH) to non-polar xenobiotic compounds to form water-soluble metabolites. Despite the low level of sequence similarity, the different GST classes follow the same canonical fold. hGSTP1-1 belongs to the Pi class and is involved in detoxification, as well as other non-classical roles such as regulating the MAP kinase pathway, protecting cells from nitrosative stress and regulating the function of 1-Cys peroxiredoxin. The structure, function and stability of GSTP1-1 was characterised to gain a better understanding of the general characteristics of the enzyme. The heterologous expression of hGSTP1-1 in Escherichia coli produces high yields of the enzyme that is then purified using immobilised metal affinity chromatography. A GSH-CDNB conjugation assay shows that the enzyme catalyses this reaction with a specific activity of 55.5 μmol/min/mg. The enzyme also binds 8-anilinonaphthalene-1-sulfonic acid (ANS), resulting in a blue shift and a two-fold increase in the fluorescence intensity of ANS. Far-UV circular dichroism shows that hGSTP1-1 is a predominantly alpha-helical protein, while intrinsic fluorescence studies show that the enzyme has Trp residues. Studies done using size exclusion HPLC show that the protein adopts a monomeric structure when exposed to high salt concentrations. Thermal unfolding of hGSTP1-1 shows that the enzyme unfolds irreversibly when exposed to increasing temperatures. Urea denaturation of the enzyme follows a two-state model (N2 ↔ 2U) and shows that domain 1 and domain 2 unfold in a cooperative manner.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements in fulfilment of the degree for Master of Science. October 2018
Keywords: Glutathione transferase; Isoleucine